The House Divided Against Itself: Youth and Electoral Violence in Nigeria - Jeremiah O. Omotayo (Universitas Medan Area, 2022)
The assumption that youths are veritable tools in engineering electoral violence has long been established in Nigeria politics. Many of the elections held in the country at federal, state and local levels where violence had erupted, had behind the scenes youths as perpetrators. While some keep making themselves available to selfish individuals and organisations who empowers them to make elections tensed, hindering citizens, especially young ones from freely exercising their civic responsibilities, this is only a fraction of the Nigerian youth population and not the whole. There are more youths who are willing to join the electoral exercise but have become apolitical partly because of threats to their lives and properties if they participated in the electoral process. There have been cases were serving youth corps members, officiating during elections have been attacked and killed by fellow youth, likewise youth who have gone out to vote. Interestingly, Nigeria has a burgeoning young population with more than 70 percent under the age of 40. For peaceful elections and for representative democracy, the youth have a pivotal part to play. Hence, they are both the cause for and the cure against electoral violence in Nigeria. This paper, using desk research, seeks to go beyond the narrative of youth being used as tools to cause violence during elections to argue that the effects of their actions hamper in no small measure the impact their population is able to make in terms of national development and representative democracy.